The Songs and rituals of the Finno-Karelian bear hunt : Gifts, seduction and mimesis in the forest - Piludu, Vesa Matteo (2024)
In this chapter, I analyse the first stage of Finnish and Karelian bear ceremonialism – the songs and rituals performed during the bear hunt in the forest. First, I present the whole structure of Finno-Karelian ceremonialism and its socio-economic, cultural, and religious backgrounds. I examine the conceptions of the bear and the forest in Finno-Karelian folk belief, emphasising the importance of the personalisation of the forest and the bruin – the bear. The forest was considered a mythical world with a social structure: Its inhabitants, the forest haltias (guardian spirits) and the bear, were considered as persons of the forest, with whom the hunters tried to establish a complex ritual relationship both during and after the hunt. After this introduction, I will analyse the songs and rituals of the bear hunt, focusing: 1) on offerings to forest spirits, 2) on seductive songs for female forest spirits, 3) on songs to wake up the bear from its hibernation in its den, which were performed before the kill, and 4) on songs that portrayed the kill as an accident and denied the hunters’ responsibility. The goal of the ritual communication during the hunt was to please the forest spirits and to avoid the revenge of the bears. My interpretation is based on theoretical reflections: 1) on the personhood of the bear and forest spirits, ontology, animism, and human-environmental ritual relations, and 2) on the status of the hunter as a mimetic suitor and groom of female forest spirits and bears. Keywords: Finnish and Karelian bear ceremonialism, ritual hunt, ontology, animism, personalisation of forest and bear, mimesis, ritual seduction Peer reviewed